Floricultural products : a study of major markets (Geneva : International Trade Centre UNCTAD?GATT, 1987)
The study covers non-flowering (green) foliage plants, fresh decorative cut foliage, and fresh cut flowers.
The preparation and publication of this study was financed by a grant to the international Trade Centre UNCTAD/GATT from the Government of Norway.
rpm 24/01/2019
Loans
Keywords: Flowers; Ornamental plant industry; Cut flower industry; Cut folliage industry